UNA LECTURA CRÍTICA DE DON JOSÉ FIGUERES FERRER. EN TORNO A LA GUERRA CIVIL DE 1948 Y SU PAPEL EN LA JUNTA FUNDADORA DE LA SEGUNDA REPÚBLICA - Contreras, Gerardo (2008)
This study aims to construe the role played by José Figueres Ferrer, popularly known as Don Pepe, during a crucial period in Costa Rican political history. The author analyzes the background and fundamentals of why a series of social reforms was implemented during the 1940s, which contributed to substantially improving the level of human development in the Costa Rican society.